Relação da área de gordura visceral com a doença hepática gordurosa não alcoólica - Cortés, Margarita Alexandra Peña (2021)
Introduction: obesity and non-alcoholic fatty liver disease (NAFLD) cause harm to personal health, interfere with the individual's quality of life and entail high costs for the public health system. Visceral fat is closely related to the development of a myriad of metabolic abnormalities and is associated with NAFLD. Objective: to investigate the association between visceral fat area and non-alcoholic fatty liver disease in patients with obesity. Method: crosssectional study with retrospective data collection. The sample consisted of obese patients, of both sexes, over 18 years old, candidates for bariatric surgery between July 2015 and July 2017 at COM/HSL/PUCRS. Anthropometric data and visceral fat area were evaluated using multi-frequency bioimpedance. Smoking and comorbidity variables were also analysed. NAFLD was evaluated by liver biopsy. The significance level adopted was 5% (p≥0.05) and statistical analyses were performed using the SPSS version 21.0 program. The study was approved by the Research Ethics Committee of PUCRS - CAAE 51992321.0.0000.5336. Results: 369 participants were included, mostly women (79.4%), with a mean age of 39.2 ± 10.6 years and mean BMI of 45 ± 7.1 kg/m². No statistically significant association with NAFLD was found. There was a positive association (p<0.001) between % body fat and visceral fat area. There was a positive correlation (p<0.001) between steatohepatitis and waist circumference. There was an association (p<0.001) between type II diabetes mellitus, metabolic syndrome and systemic arterial hypertension with NAFLD. Conclusion: The association between NAFLD and visceral fat area was not confirmed. The percentage of body fat proved to be an alternative to assess visceral fat. Waist circumference is a risk factor for the evolution of NAFLD. New studies with more robust designs must be carried out to confirm or refute the results of this study.